Synthesis of elevated temperature CO2 adsorbents from aqueous miscible organic-layered double hydroxides - Zhu, X; Chen, C; Suo, H; Wang, Q; Shi, Y; O'Hare, D; Cai, N (Elsevier, 2018)
Layered double oxides (LDOs), which derives from the calcination of layered double hydroxides (LDHs), are a type of elevated temperature CO 2 adsorbents for pre-combustion carbon capture. Due to its highly aggregated stone-like structure, the CO 2 capture capacity of commercial MgAl-CO 3 LDO is relatively low. A novel method, the aqueous miscible organic solvent treatment (AMOST), was proposed to synthesize LDH precursors with increased surface area. In this work, three types of LDHs and LDOs with different Mg/Al ratios were synthesized using the conventional and AMOST methods. The aqueous miscible organic (AMO) solvent-treated Mg 2 Al-CO 3 presented the highest CO 2 working capacity of 0.506 mmol/g at 400 °C of all the LDOs, which was 63.4% higher than that of commercial MG63. By removing the interlayered water using AMO solvent washing, the LDH was exfoliated into nanosheets and formed flower-like structures. The exposed internal surfaces increased the density of effective active sites after calcination. The AMO solvent-treated LDH also provided more alkali ion promoters for surface modification and led to better dispersion. After impregnation with 20 wt.% K 2 CO 3 , the CO 2 working capacity of the AMO solvent-treated K-Mg 3 Al-CO 3 could reach a stable value of 1.069 mmol/g at 400 °C, which was 22.9% higher than that of commercial K-MG70.